Factors Associated with Mortality in Covid-19 Patients Hospitalized in Conakrys CT-Epi, from 2020 to 2022 (Global Journal of Medical Research, 2024)
Introduction The extent of morbidity and mortality linked to the Covid-19 disease in Guinea has highlighted the need for effective and efficient preparedness and response activities to break the chain of transmission of the disease Covid-19 response activities are among the critical activities we must interrupt the chains of transmission and combat outbreaks of the disease with epidemic potential in Africa Methodology Our study population consisted of patients hospitalized in the CT-Epi of Conakry aged of all ages identified in the care database This was an analytical cross-sectional study made from the database of hospitalized people infected with Covid-19 in the CT-Epi of Conakry in Guinea in 2022 A binary logistic regression was carried out to identify the factors associated with the mortality of Covid-19 patients with comorbidity hospitalized in CT-Epi in Conakry Results In total 10 404 Covid-19 patients were included in the study Patients infected with Covid-19 in the age groups of 40-59 years 60 years and over had a risk of death increased by 3 times respectively OR 2 99 95 CI 2 17-4 10 p 0 01 and 11 times OR 11 23 95 CI 8 42-14 98 p 0 000 more than Covid-19 infected patients in the 0-39 range years adjusting for other factors Patients infected with Covid-19 who were hospitalized at CT-Epi in Gbessia compared to those hospitalized at the Donka National Hospital had a risk of death multiplied by18 OR 18 90 95 CI 13 70-26 08 p 0 000 holding the other variables constant in the model Patients infected with Covid-19 hospitalized at the CT-Epi at Camp Alpha had a 78 lower risk of dying OR 0 22 95 CI 0 09-0 50 p 0 000 compared those hospitalized at the Donka National Hospital all other things being equal Patients suffering from Covid-19 associated with diabetes alone had a 5-fold increased risk of dying OR 5 20 95 CI 2 45-11 04 p 0 000 compared to those who did not suffer from diabetes maintaining the other findings in the model Patients suffering from Covid-19 in combination with HIV alone had a 6 times increased risk of dying OR 6 59 95 CI 2 50-17 40 p 0 000 compared to those which there was no association adjusting for the other variables Patients suffering from Covid-19 and several comorbidities had a twice as high risk of dying OR 2 57 95 CI 1 66-4 4 00 p 0 000 compared to those which had not adjusting for the other variables Conclusion During the emergencies of the Covid-19 outbreak in Guinea the proportion of deaths due to comorbidities was 43 7 The response to the outbreak through the dispatch of mixed teams and the management of confirmed cases and the strengthening of epidemiological surveillance has reduced the risk of transmission of the virus in the country The factors that determine morbidity and mortality are age CT-Epi diabetes HIV several comorbidities
Keywords: covid-19; comorbidities; CT-Epi conakry; binary regression